2000
DOI: 10.1046/j.1460-9592.2000.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hemodynamic Instability in Paroxysmal Supraventricular Tachycardia: Noninvasive Evaluations by Head‐Up Tilt Testing and Power Spectrum Analysis on Electrocardiographic RR Variation

Abstract: Hemodynamic instability is a crucial determinant of the best therapeutic option in paroxysmal supraventricular tachycardia (PSVT). However, it is still unclear if hemodynamic instability is tachycardia dependent or independent. We performed frequency-domain analysis of electrocardiographic RR variations during induced PSVT and head-up tilt tests after successful ablation to investigate the role of autonomic vasomotor function in hemodynamic instability during PSVT. Thirty-six patients with (syncope group, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(45 reference statements)
1
5
0
1
Order By: Relevance
“…A heart rate over 170 beats/min was the major factor that was associated with syncope among 167 patients with SVT (Wood et al., 1997). In line with this study and in agreement with the tachycardia rates observed in our patients on ILR, two reports underline that an extremely rapid heart rate during tachycardia is a sufficient condition for the induction of significant hemodynamic changes (Doi et al., 2000; Paul et al., 1990). On the contrary, the induction of high ventricular rate tachyarrhythmia in EPS was well tolerated in Wolff–Parkinson–White patients with a syncope history, suggesting that fast SVT is not necessary a syncope risk factor (Auricchio et al., 1991).…”
Section: Discussionsupporting
confidence: 92%
“…A heart rate over 170 beats/min was the major factor that was associated with syncope among 167 patients with SVT (Wood et al., 1997). In line with this study and in agreement with the tachycardia rates observed in our patients on ILR, two reports underline that an extremely rapid heart rate during tachycardia is a sufficient condition for the induction of significant hemodynamic changes (Doi et al., 2000; Paul et al., 1990). On the contrary, the induction of high ventricular rate tachyarrhythmia in EPS was well tolerated in Wolff–Parkinson–White patients with a syncope history, suggesting that fast SVT is not necessary a syncope risk factor (Auricchio et al., 1991).…”
Section: Discussionsupporting
confidence: 92%
“…reported that neglecting other tachyarrhythmias may be the cause of hemodynamic instability. [ 15 ] The result of 24-h Holter monitoring in the study showed that there were no significant differences in SDNN, SDANN, Max HR, Min HR, and mean HR before and after ablation, but some studies showed change in autonomic tone in patients with PSVT after HUTT. [ 1 25 26 ]…”
Section: Discussionmentioning
confidence: 98%
“…Other studies reported that autonomic dysfunction during AVNRT is influenced by induced position. [ 20 21 22 ] The same incidence of syncope and presyncope symptoms in patients with negative and positive HUTT before RFCA, unlike the study of Doi, [ 15 ] showed that HUTT before RFCA cannot predict the occurrence of syncope in patients with PSVT. However, further studies with larger sample size are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rapid rate of tachycardia or association of tachycardia with sinus node dysfunction can be expected in older patients to cause presyncope or syncope, this was not the case in our patient. It has been suggested that the neurocardiogenic mechanism is probably the most frequent cause of loss of consciousness in these cases (5,8–11). In patients with supraventricular tachycardia associated with presyncope or syncope, signs of vasovagal excessive tone, such as a higher frequency of need for isoproterenol infusion for induction of tachycardia, positive vagal maneuvers and occurrence of sinus bradycardia and/or decrease in systolic arterial blood pressure at the termination of tachycardia, were noted as compared to patients with supraventricular tachycardia without a history of presyncope or syncope (5).…”
Section: Discussionmentioning
confidence: 99%